2022
DOI: 10.1002/ehf2.13845
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine prevents disease progression in viral myocarditis via modulating the NLRP3 inflammasome in the cardiosplenic axis

Abstract: AimThe acute phase of a coxsackievirus 3 (CVB3)-induced myocarditis involves direct toxic cardiac effects and the systemic activation of the immune system, including the cardiosplenic axis. Consequently, the nucleotide-binding oligomerization domain-like receptor pyrin domain-containing-3 (NLRP3) inflammasome pathway is activated, which plays a role in disease pathogenesis and progression. The anti-inflammatory drug colchicine exerts its effects, in part, via reducing NLRP3 activity, and has been shown to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Pyroptosis, a form of inflammation programmed cell death, is involved in either inflammatory or non-inflammatory heart disease ( 65 , 66 ). NLRP3 inflammasome activation plays a significant role in initiating inflammatory response and pyroptosis, contributing to cardiac injury and dysfunction in both ischemic and inflammatory heart disease ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroptosis, a form of inflammation programmed cell death, is involved in either inflammatory or non-inflammatory heart disease ( 65 , 66 ). NLRP3 inflammasome activation plays a significant role in initiating inflammatory response and pyroptosis, contributing to cardiac injury and dysfunction in both ischemic and inflammatory heart disease ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis procedure mediated by GSDMD cleavage has a detrimental effect on cardiac function ( 70 ). Inhibitors of NLRP3 inflammasome-related pro-inflammatory factors and depletion of pyroptosis by knocking out NLRP3 or other components of NLRP3 inflammasome (ASC, GSDMD, or caspase-1) attenuate cardiac injury and improve cardiac function ( 67 , 68 , 70 - 72 ). Our observation in the present study also indicated the involvement of NLRP3 inflammasome activation in LPS-induced cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A course of doxycycline 200 mg stat and 100 mg twice daily for 10 days was commenced to treat the infective consolidation. Colchicine 500 micrograms once daily and ibuprofen 400 mg three times a day were commenced to treat the myopericarditis [ 7 ]. Her lupus medications, prednisolone 5 mg once daily and hydroxychloroquine alternating between 200 mg and 400 mg once daily, were continued.…”
Section: Managementmentioning
confidence: 99%
“…IL-1ß is generated by the Nod-like receptor protein 3 (NLRP3) inflammasome, a multiprotein complex, part of the innate immunity, which gets activated following dangerous associated molecular patterns, like the alarmins S100A8 and S100A9 ( 18 , 19 ), tobacco ( 20 ) and cholesterol crystals ( 21 ), as well as by pathogen associated molecular patterns (PAMPs), like coxsackievirus B3 ( 22 , 23 ) and human papillomavirus ( 24 ), covering a broad spectrum of triggers present in or provoking both CVD/heart failure and cancer ( 25 ). Oxidized LDL and cholesterol crystals are DAMPs which activate the NLRP3 inflammasome and lead to IL-1ß secretion.…”
Section: Convergence Of Inflammation and Immune Cell Disbalance In Cv...mentioning
confidence: 99%